SARS-CoV-2 infection in pregnancy: clinical characteristics and vertical transmission in a reference hospital in Peru - Urbina-Alvarez, Claudia Aracelli (2024)
The study carried out in the Department of Gynecology and Obstetrics of the Edgardo Rebagliati Martins National Hospital (HNERM) aimed to analyze the vertical transmission of the SARS-CoV-2 virus in pregnant women with COVID-19. Twelve pregnant women who met the established inclusion criteria were included. Real-time PCR (RT-PCR) diagnostic testing for SARS-CoV-2 was performed during the admission of each pregnant patient, and placenta samples were collected for pathological evaluation. The results showed that vertical transmission of the virus was rare, with an overall low positivity rate in newborns. Although the study has limitations, such as the small number of cases and the lack of electron microscope analysis, it constitutes the first attempt in Peru to evaluate vertical transmission. It is concluded that more research is needed to better understand the relationship between COVID-19 infection and complications during pregnancy.